Linguistic minorities in court : the exclusion of indigenous peoples in Brazil - Vitorelli, Edilson (Language and Law / Linguagem e Direito, 2017)
The main purpose of this study is to demonstrate how Brazilian Courts have contributed to the process of destruction of indigenous languages in Brazil. The history of Brazilian indigenous populations, just as in other countries, is a history of violence, persecution and murder. Only recently Brazil has adopted laws that would enable effective protection of the Indians and their culture. However, the strict interpretation of these laws, adopted by Brazilian Courts, is resulting in restrictions of the rights of the Indians, among them, the right to express themselves in their own language. This situation reached a climax in the recent Verón case, in which Indians who witnessed a homicide were prevented from testifying in their own language, because they were also able to express themselves in Portuguese. As I will demonstrate, there is scientific evidence that such ruling, if it had been enforced, would have potential to cause misunderstandings and misinterpretation of the report provided by the witnesses. At the conclusion, I seek to demonstrate how other countries, notably Canada, Ireland and Australia, are dealing with this situation more adequately than Brazil, ensuring linguistic diversity and the protection of Indians and their culture.